2021
DOI: 10.1371/journal.pone.0246733
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming TRAIL-resistance by sensitizing prostate cancer 3D spheroids with taxanes

Abstract: Three-dimensional spheroid cultures have been shown to better physiologically mimic the cell-cell and cell-matrix interactions that occur in solid tumors more than traditional 2D cell cultures. One challenge in spheroid production is forming and maintaining spheroids of uniform size. Here, we developed uniform, high-throughput, multicellular spheroids that self-assemble using microwell plates. DU145 and PC3 cells were cultured as 2D monolayers and 3D spheroids to compare sensitization of TRAIL-resistance cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We used human prostate cancer PC3 and DU145 cells (both purchased from American Type Culture Collection) which exhibit high and medium sensitivity to TRAIL, respectively, to compare the apoptotic activity of the phase-separated liposomes conjugated with different numbers of TRAIL molecules. 24 Our previous studies found that each of these two cell lines expresses both DR4 and DR5, with a higher expression of DR5 than DR4. 25 In both of the cell lines, the TRAIL liposomes showed higher cytotoxic effects than free TRAIL after 24 h of treatment.…”
Section: Cytotoxicity Of Phase-separated Trail Liposomesmentioning
confidence: 82%
“…We used human prostate cancer PC3 and DU145 cells (both purchased from American Type Culture Collection) which exhibit high and medium sensitivity to TRAIL, respectively, to compare the apoptotic activity of the phase-separated liposomes conjugated with different numbers of TRAIL molecules. 24 Our previous studies found that each of these two cell lines expresses both DR4 and DR5, with a higher expression of DR5 than DR4. 25 In both of the cell lines, the TRAIL liposomes showed higher cytotoxic effects than free TRAIL after 24 h of treatment.…”
Section: Cytotoxicity Of Phase-separated Trail Liposomesmentioning
confidence: 82%
“…In contrast to our 2016 orthotopic prostate tumor study, TRAIL liposomes were unable to reduce primary tumor volume [ 35 ]. Recent data suggests DU145 cells are TRAIL resistant and show very minimal apoptosis in 2D and 3D cultures when treated with TRAIL alone [ 57 , 58 ]. Tumor cells can also develop mechanisms to avoid TRAIL cytotoxicity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should investigate dosing with different concentrations of TRAIL liposomes to establish a dose response and maximum tolerated dose in mice. If necessary, EST liposomes can be combined with known TRAIL sensitizers such as taxanes [ 57 , 58 ] curcumin [ 59 ], piperlongamine [ 60 ], or Yoda1 [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…One way in which TRAIL can become sensitized is through the fluid shear stress (FSS) that CTCs experience in the circulation . Alternatively, under static conditions, TRAIL resistance can be overcome with molecular therapeutics using molecules such as aspirin, taxanes, and piperlongumine. Previous studies have found that the activation of the mechanosensitive ion channel Piezo1 via the agonist Yoda1 also induces TRAIL sensitization under static conditions and have characterized the toxicity of this treatment using HUVEC cells as a non-cancerous control. , The mechanism by which the small-molecule Yoda1 activates Piezo1, a mechanosensitive Ca 2+ ion channel, is currently unknown. However, Ca 2+ influx through Piezo1 is known to lead to a number of cellular responses, including apoptosis . In vivo, Yoda1 was found to cause a significant increase in apoptosis in prostate cancer, breast cancer, and colon cancer cell lines compared to TRAIL alone …”
Section: Introductionmentioning
confidence: 99%